Contaminación por staphylococcus aureus en el procesamiento de un embutido fermentado portugués (linguiça) - Cadavez, Vasco (2018)
Linguiça is a Portuguese dry-fermented sausage, which has been found to harbour food-borne pathogens in the past. Hence, the objective of this study was to investigate the levels of total viable counts (TVC), Enterobacteriaceae, and S. aureus at the key production stages of linguiça by depicting their changes using principal component analysis. Unlike Enterobacteriaceae counts, which decreased from raw meat to final product, S. aureus increased significantly in the meats throughout processing. While Enterobacteriaceae was very sensitive to the decrease in water activity, S. aureus remained viable and developed during fermentation. The presence of S. aureus at all stages should prompt industries to reinforce good hygiene practices in the processing of linguiça.